Improving Students’ English-Speaking Skills Through Behavior Modification in Indonesian Islamic Boarding Schools - A, Izzuddin (IJET (Indonesian Journal of English Teaching), 2018)
A number of modern Islamic Boarding Schools (IBS) have long implemented a unique English Language Teaching (ELT) strategy in improving their students’ English-speaking skills. In IBS, for example, head of language department requires the students to communicate in English in daily activities, and punishment is imposed to those who do not speak English. However, there was no specifically academic term used to describe such strategy, nor was there a study to investigate the effectiveness of the strategy. This essay investigates what IBS-applied ELT strategy is, and to what extent it is effective in improving speaking skills of the students. It is found that IBS has made use of a behaviour modification as ELT strategy. The behaviour modification is able to encourage students to communicate in English in their daily activities. It also leads students to acquire accuracy, complexity and fluency in speaking.